Pemahaman Keagamaan Terhadap Moderasi Beragama Mahasiswa Program Studi Pendidikan Agama Islam - Nurulhajj, Fadilah Arfan; Ridwan, Inayatillah; Saepudin, Asep (Moderasi : Journal of Islamic Studies, 2023)
This research covers three main aspects, namely the understanding, responses, and religious influence of Islamic religious education study program students on religious moderation. This research uses quantitative research methods and data collection techniques through the distribution of questionnaires, observation, interviews, and documentation. The population and sample in the study included all students of the Islamic religious education study program at STIT At-Taqwa Ciparay-Bandung, using non-probability sampling techniques.The research results show that students' religious understanding is included in the good category, with a frequency of 57 and a percentage of 68%. Meanwhile, religious moderation is included in the quite good category, with a frequency of 39 and a percentage of 46%. Apart from that, the research results also revealed that around 33.1% of the level of religious moderation was influenced by religious understanding, while the remainder, around 66.9%, was influenced by other variables not studied, such as seminar training programs, curriculum based on religious understanding, extracurricular activities. based on religious understanding, mentoring and spiritual guidance, religious studies, integration of religious values in campus life, and so on. This research is important in the context of efforts to increase religious moderation in society.